PERKEMBANGAN KARIR PADA MILENIUM BARU DALAM KONSEP PENGELOLAAN EMOTIONAL INTELLIGENCE GUNA MENDUKUNG MOBILITAS KARIR - Gusti, Yenni Kurnia (Universitas Slamet Riyadi, 2004)
ABSTRACT Career managerial get change together with expanding organization chart. In early millennium, various changes will be non-stopped to emerge accompany the turn of century. The century 21 estimated will bring various elementary changes in organization. Pattern of Career managerial will change to accompany the organizational change. Companies make the career planning for the sake of with, because career planning of concerning organizational future and opportunity developing of all employees. A new model of career tries to place return at more vital portion, but new model goodness and also old fashion own the character element, which often disagree with the fact of last and now. Current trend in organization has impact for the psychological change of individual and improvement to HRD. At the moment most executive have earned to accept fully that emotional intelligence (EI) is something that necessary for individual effectiveness. The building of strong team require to emphasize new research include the emotional intelligence (EI) at one particular group and how to reach for the EI with as effective as possible. Real matter which can be perceived that the impact of emotional intelligence to mobility of somebody career. Evaluate to aspect from mobility of itself career need to be perceived, its meaning is career development in a organization more focus in perspective of person and organizational also cope to understand everything which is concerning mobility process, inclusive issue of change and issue, and also requirement utilize to consider various issue of business and change to career planning Keywords: Career of 21st century, Emotional Intelligence, Career Mobility